2006
DOI: 10.2353/ajpath.2006.050636
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Infection Reveals a Novel Regulatory Role for Galectin-3 in the Interface of Innate and Adaptive Immunity

Abstract: In attempts to investigate the role of galectin-3 in innate immunity, we studied galectin-3-deficient (gal3 ؊/؊ ) mice with regard to their response to Toxoplasma gondii infection, which is characterized by inflammation in affected organs, Th-1-polarized immune response, and accumulation of cysts in the central nervous system. In wild-type (gal3 ؉/؉ ) mice, infected orally, galectin-3 was highly expressed in the leukocytes infiltrating the intestines, liver, lungs, and brain. Compared with gal3 ؉/؉ , infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
103
1
8

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 55 publications
10
103
1
8
Order By: Relevance
“…These results indicate that the bacterial clearance in the early course of R. equi infection was more efficient in gal3 À/À mice compared with gal3 1/1 mice. Gal3 À/À mice develop a delayed but increased inflammatory response compared with gal3 1/1 mice It was previously shown that galectin-3 expression is upregulated during allergic airway inflammation [28] and Toxoplasma gondii infection [29]. Here, we found an increase in galectin-3 staining in the liver and spleen from the gal3 1/1 mice that had been intravenously inoculated with R. equi ( Fig.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…These results indicate that the bacterial clearance in the early course of R. equi infection was more efficient in gal3 À/À mice compared with gal3 1/1 mice. Gal3 À/À mice develop a delayed but increased inflammatory response compared with gal3 1/1 mice It was previously shown that galectin-3 expression is upregulated during allergic airway inflammation [28] and Toxoplasma gondii infection [29]. Here, we found an increase in galectin-3 staining in the liver and spleen from the gal3 1/1 mice that had been intravenously inoculated with R. equi ( Fig.…”
Section: Resultssupporting
confidence: 55%
“…It has been difficult to address the exact mechanism underlying the proinflammatory role of galectin-3. Several authors have reported that the absence of galectin-3 affects the migration of macrophages, eosinophils, neutrophils and lymphocytes in a different way, depending on the experimental conditions [14,28] and the organ examined [29]. In the present study, gal3 À/À mice also exhibited an attenuated inflammatory response in the liver during the first 24-48 h postinfection, which was not associated with higher bacterial burdens.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations